EVALUASI PROGRAM BAITUL ARQAM BAGI KARYAWAN DI UNIVERSITAS MUHAMMADIYAH PALANGKARAYA - Nurul Hikmah Kartini (Anterior Jurnal, 2017)
The University of Muhammadiyah Palangkaraya routinely conducts the cadre program to its employees held every month of Ramadan called Baitul Arqam. The problems faced in this institution are not all employees understand about Al-Islam and Kemuhammadiyahan which are implemented in daily life and worship. Baitul Arqam program is one of the solutions run by the institution to answer the problem. As a program that has been running for more than 3 (three) years, it is necessary to evaluate. This evaluation aims to identify the effectiveness of Baitul Arqam Program for Employees at The University of Muhammadiyah Palangkaraya. This study uses CIPP evaluation model. Stufflebeam's CIPP evaluation model focuses on four aspects: context, input, process, and product. Data collection by using interviews, observation, and documentation. Study subjects that are used as data sources of information are Rector, Vice Rector I, Vice Rector II, Head of LPPKK, Presenters, and Participants / employees at The University of Muhammadiyah Palangkaraya with a sample of 80 people. Evaluation results show: 1) Analysis of needs and goals and objectives of the program on the component context is in very good category. ; 2) Planning strategies covering materials, human resources, facilities and infrastructure, funding, and learning methods in the inputs component of BBTHA program at The University of Muhammadiyah Palangkaraya are included in good category; 3) In the process components implemented in the program Baitul Arqam For Employees included in good category; 4) In the product components produced Baitul Arqam program For Employees included in good category.